Developmental endothelial locus-1 protects from hypertension-induced cardiovascular remodeling via immunomodulation - Theresa Failer; Michael Amponsah-Offeh; Aleš Neuwirth; Ioannis Kourtzelis; Pallavi Subramanian; Peter Mirtschink; Mirko Peitzsch; Klaus Matschke; Sems M. Tugtekin; Tetsuhiro Kajikawa; Xiaofei Li; Anne Steglich; et al. (The Journal of Clinical Investigation, 2022)
The causative role of inflammation in hypertension-related cardiovascular diseases is evident and calls for development of specific immunomodulatory therapies. We tested the therapeutic efficacy and mechanisms of action of developmental endothelial locus-1 (DEL-1), an endogenous antiinflammatory factor, in angiotensin II– (ANGII–) and deoxycorticosterone acetate–salt–induced (DOCA-salt–induced) cardiovascular organ damage and hypertension. By using mice with endothelial overexpression of DEL-1 (EC-Del1 mice) and performing preventive and interventional studies by injecting recombinant DEL-1 in mice, we showed that DEL-1 improved endothelial function and abrogated aortic adventitial fibrosis, medial thickening, and loss of elastin. DEL-1 also protected the mice from cardiac concentric hypertrophy and interstitial and perivascular coronary fibrosis and improved left ventricular function and myocardial coronary perfusion. DEL-1 prevented aortic stiffness and abolished the progression of hypertension. Mechanistically, DEL-1 acted by inhibiting αvβ3 integrin–dependent activation of pro-MMP2 in mice and in human isolated aorta. Moreover, DEL-1 stabilized αvβ3 integrin–dependent CD25+FoxP3+ Treg numbers and IL-10 levels, which were associated with decreased recruitment of inflammatory cells and reduced production of proinflammatory cytokines in cardiovascular organs. The demonstrated effects and immune-modulating mechanisms of DEL-1 in abrogation of cardiovascular remodeling and progression of hypertension identify DEL-1 as a potential therapeutic factor.